AB0855 Identifying patients with axial spondyloarthritis by data mining mri radiology reports. (12th June 2018) - Reilly, E.; Szachowicz, A.; Sengupta, R.
Abstract : Background: Axial Spondyloarthritis (axSpA) encompasses ankylosing spondylitis (AS) and non radiographic axSpA (nr-axSpA) as part of the ASAS classification criteria 1 2 . The role of MRI is now central in identifying patients early in the disease course 3, but our use of this needs to be standardised to ensure appropriate requesting and correct interpretation of MRI axSpA features. Objectives: ( 1 To identify the MRI protocols used to investigate patients with back pain ( 2 To describe the prevalence of axSpA associated spinal lesions in patients with known axSpA ( 3 To describe the prevalence of axSpA associated spinal lesions in patients with back pain and their relevance in subsequently diagnosed axSpA Methods: MRI reports between 4th January 2015 and 25th February 2017 containing the key words 'ankylosing spondylitis' (AS), 'bone marrow oedema' (BMO), 'spondyloarthritis' and 'sacroiliitis' were identified using a computerised word finding programme, in a tertiary referral hospital for Rheumatology. Results: 194 patients had MRI features of axSpA. 60.8% were female; mean age 39.3 years (SD 13.3). 96.4% (n=187) contained the term 'sacroiliitis', with 'AS, 'BMO' and 'spondyloarthritis' in 2.6%, 0.5% and 0.5% respectively. 63.4% were referred by a rheumatologist, and 19.1% from primary care. Musculoskeletal radiologists reported 16.0%, general radiologists 37.1%, and external radiology services 46.4%. The most common MRI protocol was the inflammatory spinal protocol (ISP-MRI, 57.2%), with sacroiliac (SIJ) MRI in 17%. 87.4% ISP-MRI and 48.5% MRI SIJ were requested by Rheumatology. GPs requested more ISP-MRI than other sequences (29.7% of their total MRIs). 144 cases had a diagnosis stated on the MRI request; 100 (69.4%) had an existing diagnosis of axSpA, and 20 (13.9%) of a peripheral arthritis. In patients with known AxSpA, the most frequent findings were BMO (70.3%), and erosions (67%). Ankylosis was only seen in 4 patients. Features of axSpA were identified in 26 MRIs requested for mechanical back pain, and 11 for unrelated medical reasons. 33 cases of BMO and 29 of SIJ erosions were identified in patients who did not have a pre existing diagnosis of AxSpA, and one showed ankylosis. 16 patients went on to have a diagnosis of axSpA. Conclusions: Through data mining of MRI reports, we have found that appropriate MRI sequences are being requested when features of AxSpA are suspected. The rate of chronic features of AxSpA such as ankylosis was low, suggesting this cohort may have short disease durations. Multiple features of AxSpA were identified in patients without an existing diagnosis prior to imaging. 16 new cases of AxSpA were identified. References: [1] Rudwaleit M, van der Heijde D, Landewé R, et al, The development of assessment of spondyloarthritis international society classification criteria for axial spondyloarthritis (part II): validation and final selection. Ann Rheum Dis2009; 68:77783.doi:10.1136/ard.2009.108233, [2 Baraliakos X, Braun J] Non-radiographic axial spondyloarthritis and ankylosing spondylitis: what are the similarities and differences?RMD Open 2015;1:e000053.doi:10.1136/rmdopen-2015-000053. [] 3Hoffstetter Pet al, Magnetic Resonance Imaging of the Axial Skeleton in Patients With Spondyloarthritis: Distribution Pattern of Inflammatory and Structural Lesions, Clin Med Insights Arthritis Musculoskelet Disord. 2017; 10: 1179544117728081, Published online 2017Aug 29. Disclosure of Interest: None declared